(untitled) (KULT_online, 2010)
The 267 page-anthology Angeschwemmt-Fortgeschrieben – Robinsonaden im 20. und beginnenden 21. Jahrhundert (Washed Ashore – Updated – Robinson Crusoe Themes in the 20th and early 21st century) edited by Ada Bieber, Stefan Greif and Günter Helmes contains thirteen articles. In a manner as concise as it is comprehensible, the book shows the continued omnipresence of the Robinson figure in today’s literary and cultural studies. Contributors analyse canonic literary works – such as William Golding’s Lord of the Flies – but also relatively unknown and rarely reviewed novels, audio books and films.